2013
DOI: 10.1038/aja.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean ginseng berry extract (GB0710) on penile erection: evidence from in vitro and in vivo studies

Abstract: Several reports have promoted the root-derived Korean red ginseng (KRG; Panax ginseng) as alternative treatment for erectile dysfunction (ED), and ginsenosides are known to be the principal active ingredients of ginseng. Recent studies showed that ginseng berries produce more ginsenosides than KRG; thus, we investigated the ability of the Korean ginseng berry extract GB0710 to relax the penile corpus cavernosum smooth muscle (CCSM) in this study. As a comparative control, the results were compared to those obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Sperm count and motility were also increased in treated male rats [51]. The fact that Cho et al [52] demonstrated that the relaxation effect of ginseng berry extracts on corpus cavernosum smooth muscle can be partially reduced by pre-treating the tissue with various NO inhibitors seems to support these demonstrations. In addition to this, from a study by Hong et al [53] on patients with untreated ED (double-blind, placebo-controlled), it has been shown that Korean red ginseng can improve the scores for erectile function (60% of the treated patients, vs. 20% of the ones treated with placebo), sexual desire, and intercourse satisfaction.…”
Section: The Old Made New: Traditional Medicinementioning
confidence: 81%
“…Sperm count and motility were also increased in treated male rats [51]. The fact that Cho et al [52] demonstrated that the relaxation effect of ginseng berry extracts on corpus cavernosum smooth muscle can be partially reduced by pre-treating the tissue with various NO inhibitors seems to support these demonstrations. In addition to this, from a study by Hong et al [53] on patients with untreated ED (double-blind, placebo-controlled), it has been shown that Korean red ginseng can improve the scores for erectile function (60% of the treated patients, vs. 20% of the ones treated with placebo), sexual desire, and intercourse satisfaction.…”
Section: The Old Made New: Traditional Medicinementioning
confidence: 81%
“…In animal studies, treatment with Korean red ginseng and ginseng berry extract has been shown to significantly relax the pre-contracted penile corpus cavernosum smooth muscles of rabbits in vitro, and increase the intracavernosal pressure of rats in vivo 9 , 10 . Data from studies on ginseng berry extract suggest that this action is nitric oxide (NO) dependent.…”
Section: Sex Performancementioning
confidence: 99%
“…Red ginseng stimulates NO synthase, increasing the production of NO and blood flow into the corpora cavernosa. Studies in rabbit models have shown dose-dependent relaxation of smooth muscle within the corpora cavernosa as well as an increase in intracavernosal pressure 76 . It has been proposed that Ginkgo biloba induces production of NO in endothelial cells while simultaneously relaxing vascular smooth muscle cells.…”
Section: History Of Ed Treatmentmentioning
confidence: 99%